Composite current collector, composite pole piece, lithium battery and preparation method

By setting a crosslinking film between the organic substrate and the conductive layer of the composite fluid collector, the problem of low crosslinking performance of each layer of the composite fluid collector is solved, the mechanical strength and bonding performance are significantly improved, and the performance and stability of the lithium battery are improved. sex.

CN119447314APending Publication Date: 2025-02-14ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410443347.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2024-04-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing composite liquid collector has low cross-linking performance between the layers and is unstable, and is easily peeled off or shed under external forces, affecting the energy density and performance of lithium batteries.

Method used

A crosslinked film is provided between the organic substrate and the conductive layer. The crosslinked film is obtained by adding an adhesive, a modifier and a thickener to the solvent by mechanical stirring through ultrasonic combination, and is coated and heated. The curing formation enhances the mechanical properties of the organic substrate and the bonding properties of the conductive layer.

Benefits of technology

It significantly improves the mechanical strength of the composite fluid collection and the binding performance of the conductive layer with the organic substrate. The longitudinal tensile strength MD≥240MPa and the transverse tensile strength TD≥200MPa, avoiding the risk of conductive layer falling off and improving the performance of lithium batteries. and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447314A_ABST
    Figure CN119447314A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector, a composite pole piece, a lithium battery and a preparation method. The composite current collector comprises an organic matter substrate, a cross-linked thin film provided on at least one side of the organic substrate and configured to have the cross-linking performance of the organic substrate; the conductive layer is arranged on one side, far away from the organic matter substrate, of the cross-linked film; wherein the cross-linked film is formed by coating at least one side of the organic matter substrate with a prepolymer solution, the prepolymer solution is obtained by adding an adhesive, a modifier and a thickener into a solvent and performing ultrasonic and mechanical stirring at normal temperature, the adhesive is used for enhancing the viscosity of the prepolymer solution, and the modifier is used for modifying the modifier. The modifier is used for enhancing the mechanical property of the organic matter substrate, and the thickener is used for adjusting the viscosity of the prepolymer solution.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to Chinese patent application No. 202310988187.X filed in China on August 7, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present disclosure relates to the field of batteries, and in particular to a composite current collector, a composite pole piece, a lithium battery and a preparation method thereof. Background Art

[0005] The current collector is one of the important components of lithium-ion batteries. Its function is to carry active materials, collect and conduct electrons. An ideal lithium-ion battery current collector should meet the following characteristics: high electrical conductivity, good chemical and electrochemical stability, high mechanical strength, good compatibility and binding force with electrode active materials, low cost and easy availability, and light weight. Traditional current collectors generally use aluminum foil as the positive electrode current collector and copper foil as the negative electrode current collector. However, copper foil and aluminum foil are difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, people have developed composite current collectors. Compared with traditional metal foils, composite current collectors have the advantages of high conductivity, low cost, and light weight.

[0006] However, the existing composite current collectors have low cross-linking performance between the layers and are unstable, and there is a risk of easy peeling or falling off when encountering external forces, which in turn affects the energy density and performance of the battery. Summary of the invention

[0007] In view of the above technical problems, the present disclosure provides a composite current collector, a composite pole piece, a lithium battery and a preparation method to solve or at least alleviate at least one technical problem existing in the above composite current collector, composite pole piece and lithium battery.

[0008] According to a specific embodiment of the present disclosure, the present disclosure provides a composite current collector, including:

[0009] An organic substrate and a cross-linked film disposed on at least one side of the organic substrate, wherein the cross-linked film is used to enhance the cross-linking performance of the organic substrate;

[0010] A conductive layer, disposed on a side of the cross-linked film away from the organic substrate;

[0011] The cross-linked film is formed by coating a prepolymer solution on at least one side of the organic substrate. The prepolymer solution is obtained by adding an adhesive, a modifier and a thickener to a solvent and stirring the prepolymer solution by ultrasound combined with mechanical stirring at room temperature. The adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution.

[0012] In some embodiments, the modifier includes: styrene acrylic emulsion and dimethyl acrylamide, wherein the dimethyl acrylamide is used to adjust the rigidity of the styrene acrylic emulsion, and the mass percentage of the dimethyl acrylamide in the styrene acrylic emulsion is 2%-3%.

[0013] In some embodiments, the styrene acrylic emulsion accounts for 0.5%-10% by weight of the prepolymer solution.

[0014] In some embodiments, the adhesive includes: dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea; the mass percentage of the adhesive in the prepolymer solution is 1%-5%.

[0015] In some embodiments, the thickener includes carboxymethyl cellulose, and the carboxymethyl cellulose accounts for 0.5%-5% by weight of the prepolymer solution.

[0016] In some embodiments, the thickness of the organic substrate is 4-10 μm, and the thickness of the cross-linked film is 0.3-0.8 μm.

[0017] In some embodiments, the conductive layer includes a first conductive layer and a second conductive layer, wherein the second conductive layer is located on a side of the first conductive layer close to the cross-linked film, and is used to enhance the cross-linking performance between the first conductive layer and the organic substrate.

[0018] In some embodiments, a material of the second conductive layer is aluminum oxide or copper oxide.

[0019] In some embodiments, the composite current collector is a positive composite current collector, the first conductive layer is aluminum and the material of the organic substrate is PET or BOPET, and the longitudinal tensile strength MD of the positive composite current collector is ≥240MPa, and the transverse tensile strength TD is ≥200Mpa.

[0020] In some embodiments, the composite current collector is a negative electrode composite current collector, the first conductive layer is copper and the material of the organic substrate is PP or BOPP, and the longitudinal tensile strength MD of the negative electrode composite current collector is ≥220MPa, and the transverse tensile strength TD is ≥180MPa.

[0021] In some embodiments, the negative electrode composite current collector further includes a protective film, and the protective film is located on a side of the first conductive layer away from the organic substrate.

[0022] In some embodiments, the conductive layer is symmetrically disposed on both sides of the organic substrate; and

[0023] The protection film is symmetrically arranged on two sides of the conductive layer away from the organic substrate.

[0024] In some embodiments, the cross-linking performance between the organic substrate and the conductive layer is greater than or equal to 5.0 N / 15 mm and less than or equal to 8 N / 15 mm.

[0025] According to a specific embodiment of the present disclosure, the present disclosure provides a composite pole piece, and the composite pole piece includes a composite current collector as described in any one of the above items.

[0026] According to a specific embodiment of the present disclosure, the present disclosure provides a lithium battery, comprising the composite pole piece as described above.

[0027] According to a specific embodiment of the present disclosure, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, characterized in that it comprises the following steps:

[0028] Step S1, providing an organic substrate;

[0029] Step S2, disposing a cross-linking film on at least one side of the organic substrate, configured to enhance the cross-linking performance of the organic substrate, comprising:

[0030] Step S21, adding an adhesive, a modifier and a thickener to a solvent, and obtaining a prepolymer solution by ultrasonic combined with mechanical stirring at room temperature, wherein the adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution;

[0031] Step S22, coating the prepolymer solution on at least one side of the organic substrate to form a cross-linked film;

[0032] Step S3, providing a conductive layer on at least one side of the cross-linked film away from the organic substrate.

[0033] In some embodiments, the step S1 includes: providing an organic substrate, and performing a corona treatment on the organic substrate at a power of 2500-3500W.

[0034] In some embodiments, the step S22 includes: coating the prepolymer solution on at least one side of the organic substrate by micro-gravure, and curing at 50° C.-100° C. for 3-6 minutes to form the cross-linked film.

[0035] In some embodiments, the reaction curing at 50°C-100°C for 3-6 minutes includes: first reacting and curing at 50°C-70°C for 1-2 minutes, then reacting and curing at 70°C-90°C for 1-2 minutes, and finally reacting and curing at 90°C-100°C for 1-2 minutes.

[0036] In some embodiments, step S3 includes:

[0037] Step S31, forming a second conductive layer of aluminum oxide or copper oxide on at least one surface of the cross-linked film by an in-situ reaction;

[0038] Step S32, depositing aluminum or copper on the surface of the second conductive layer away from the cross-linked film by physical vapor deposition, thereby forming a first conductive layer on the surface of the second conductive layer.

[0039] The embodiments of the present disclosure also provide a method for preparing a composite electrode, including any method for preparing a composite current collector as described above.

[0040] The embodiments of the present disclosure also provide a method for preparing a lithium battery, including any method for preparing a composite electrode as described above.

[0041] Compared with the prior art, the above solution of the embodiment of the present disclosure has at least the following beneficial effects:

[0042] The composite current collector provided by the present disclosure has a cross-linked film arranged between the organic substrate and the conductive layer. The cross-linked film is a cross-linked polymer obtained by a cross-linking polymerization reaction of an adhesive, a modifier and a thickener. The adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution, thereby improving the bonding performance between the conductive layer of the composite current collector and the organic substrate, and improving the mechanical strength of the composite current collector. The prepolymer solution does not require the addition of an initiator, and curing is simpler. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0044] Figure 1 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0045] Figure 2 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0046] Figure 3 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0047] Figure 4 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0048] Figure 5 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0049] Figure 6 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0050] Figure 7 Schematic diagram of the process of preparing a composite current collector in some embodiments of the present disclosure;

[0051] Figure 8 Schematic diagram of the process for preparing a composite current collector cross-linked film in some embodiments of the present disclosure;

[0052] Fig. 9 Schematic diagram of the process of preparing a composite current collector conductive layer in some embodiments of the present disclosure.

[0053] The reference numerals in the specific implementation manner are as follows:

[0054] Composite current collector 10;

[0055] A polymer composite layer 1, an organic substrate 11 and a cross-linked film 12;

[0056] Conductive layer 2 , second conductive layer 21 , first conductive layer 22 , protective film 23 . DETAILED DESCRIPTION

[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.

[0059] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0060] In the description of the embodiments of the present invention, the orientations or positional relationships indicated by technical terms such as "upper", "lower", and "thickness" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present invention and simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present invention.

[0061] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0062] In the description of the embodiments of the present invention, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.

[0063] Reference to "embodiments" in this disclosure means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this disclosure may be combined with other embodiments.

[0064] In the related technology, the composite current collector is still facing the following problems: On the one hand, the composite current collector obtained by directly depositing a metal layer on a polymer film by physical vapor deposition has a low crosslinking performance between the metal layer and the polymer film, which is only 0.1N / 15mm-2N / 15mm, which easily causes the risk of the metal layer peeling off or falling off from the polymer film layer. On the other hand, the surface of the polymer film is easily bombarded by metal particles in the magnetron and evaporation process, which may cause the polymer macromolecules to break and degrade locally, resulting in a significant decrease in the mechanical properties of the polymer film, resulting in weak mechanical properties of the composite current collector and causing the risk of breaking.

[0065] To this end, the present disclosure provides a composite current collector, comprising: an organic substrate; a cross-linked film, disposed on at least one side of the organic substrate, and configured to enhance the cross-linking performance of the organic substrate; a conductive layer, disposed on a side of the cross-linked film away from the organic substrate; wherein the cross-linked film is formed by coating a prepolymer solution on at least one side of the organic substrate, the prepolymer solution being obtained by adding an adhesive, a modifier and a thickener to a solvent, and by combining ultrasound with mechanical stirring at room temperature, the adhesive being used to enhance the viscosity of the prepolymer solution, the modifier being used to enhance the mechanical properties of the organic substrate, and the thickener being used to adjust the viscosity of the prepolymer solution.

[0066] Therefore, the composite current collector provided by the present disclosure is provided with a cross-linked film between the organic substrate and the conductive layer. The cross-linked film is an adhesive, a modifier and a thickener, and is obtained by ultrasonic combined with mechanical stirring at room temperature, wherein the modifier includes styrene acrylic emulsion and dimethyl acrylamide, and the adhesive includes dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea. The cross-linked film obtained can enhance the cross-linking performance between the conductive layer and the organic substrate, reaching a value greater than or equal to 5.0N / 15mm and less than or equal to 8N / 15mm, which is significantly improved compared to the binding force of 0.1N / 15mm-2N / 15mm. At the same time, the mechanical strength of the composite current collector can be improved. When the composite current collector is a positive composite current collector, the longitudinal tensile strength MD is ≥240MPa, and the transverse tensile strength TD is ≥200MPa; or, when the composite current collector is a negative composite current collector, the longitudinal tensile strength MD is ≥220MPa, and the transverse tensile strength TD is ≥180MPa.

[0067] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.

[0068] See also Figure 1The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer composite layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on both sides of the polymer composite layer 1, and the conductive layer 2 completely covers both sides of the polymer composite layer 1, that is, the conductive layer 2 covers the polymer composite layer 1 in the orthographic projection of the polymer composite layer 1. The polymer composite layer 1 comprises an organic substrate 11 and a cross-linked film 12, wherein the cross-linked film 12 is located on both sides of the organic substrate 11, and the cross-linked film 12 is located between the organic substrate 11 and the conductive layer 2.

[0069] See also Figure 2 The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer composite layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on one side of the polymer composite layer 1, and the conductive layer 2 completely covers one side of the polymer composite layer 1, that is, the conductive layer 2 covers the polymer composite layer 1 in the orthographic projection of the polymer composite layer 1. The polymer composite layer 1 comprises an organic substrate 11 and a cross-linked film 12, wherein the cross-linked film 12 is located on both sides of the organic substrate 11, and the cross-linked film 12 is located between the organic substrate 11 and the conductive layer 2.

[0070] As above Figure 1 and Figure 2 In the described embodiment, the cross-linked film 12 can enhance the cross-linking performance between the conductive layer and the organic substrate to a value greater than or equal to 5.0 N / 15 mm and less than or equal to 8 N / 15 mm. At the same time, the cross-linked film 12 can improve the mechanical strength of the composite current collector. When the composite current collector is a positive electrode composite current collector, the longitudinal tensile strength MD is ≥240 MPa, and the transverse tensile strength TD is ≥200 MPa; or, when the composite current collector is a negative electrode composite current collector, the longitudinal tensile strength MD is ≥220 MPa, and the transverse tensile strength TD is ≥180 MPa. This can solve the technical problem that the polymer film surface is bombarded by metal particles in the magnetron and evaporation process, causing the polymer macromolecules to break locally and degrade, resulting in a significant decrease in the mechanical properties of the polymer film.

[0071] The material of the organic substrate 11 is preferably a polymer film. In some embodiments, the material of the organic substrate 11 includes but is not limited to polyethylene (PE), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), biaxially oriented polyethylene terephthalate (BOPET), polyethylene terephthalate (PEN), poly(p-phenylene terephthalamide) (PPTA), polyimide (PI), polycarbonate (PC), polyetheretherketone (PEEK), polyoxymethylene (POM), poly(p-phenylene sulfide) (PPS), poly(p-phenylene oxide) (PPO), polyvinyl chloride (PVC), polyamide (PA) or polytetrafluoroethylene (PTFE). More preferably, when the composite current collector 10 is used as a positive electrode current collector, the organic substrate 11 is a PET film or a BOPET film; when the composite current collector 10 is used as a negative electrode current collector, the organic substrate 11 is a PP film or a BOPP film. Compared with PET film, BOPET film and BOPP film have better tensile strength, heat resistance, transparency and are not easy to degrade compared with PP film, which is beneficial to improve the performance of composite current collector. Since PET or BOPET is cheaper than PP or BOPP, and PET or BOPET has stronger tensile strength and heat resistance than PP or BOPP, it is the preferred substrate. Since PET or BOPET has no degradation effect on the positive electrode material aluminum, it is the preferred positive electrode material. However, when used as a negative electrode substrate, direct contact between the electrolyte and PET or BOPET will cause PET or BOPET to degrade, so it is usually not suitable to select PET or BOPET as a negative electrode substrate, and PP or BOPP is preferred as a substrate for copper. However, the binding force between PP or BOPP and copper is very low, easy to fall off, and difficult to meet the needs. Therefore, the present disclosure can enhance the binding force between PP or BOPP and copper by adding a cross-linked film 12, and at the same time, it can enhance the mechanical properties of the composite current collector.

[0072] The cross-linked film 12 is formed by a coating process of a prepolymer solution, for example, a micro-gravure coater is used to uniformly coat the prepolymer solution on the surface of a BOPET and / or BOPP film, and the cross-linked film 12 is formed by thermal curing. The cross-linked film is formed by coating a prepolymer solution on at least one surface of the organic substrate. The prepolymer solution is obtained by adding an adhesive, a modifier and a thickener to a solvent, and then subjected to ultrasonic combined mechanical stirring at room temperature. The adhesive is used to enhance the viscosity of the prepolymer solution during the cross-linking polymerization reaction. The modifier includes at least two types of organic reactants. The modifier is used to enhance the mechanical properties of the organic substrate. The thickener is used to adjust the viscosity of the prepolymer solution. As an example, for the negative electrode substrate, when copper is selected as the conductive material, PET cannot be selected as the substrate, because copper will degrade PET. When PP is selected as the substrate, the binding force between PP and copper is extremely poor. Therefore, the prepolymer solution generated by the adhesive reaction is used to enhance the binding force between the PP substrate and copper, so that PP can be well used as the negative electrode substrate. At the same time, since copper is directly deposited on the surface of the PP substrate, the polymer macromolecules will be partially broken and degraded, thereby reducing the mechanical strength of the PP substrate. Therefore, styrene-acrylic emulsion and dimethyl acrylamide are used to enhance the mechanical strength of the organic substrate. In this embodiment, the substance that reacts to generate the prepolymer solution does not require an initiator and is self-crosslinked and cured, which simplifies the difficulty of the reaction and curing. By adding an adhesive, a modifier and a thickener to a solvent, a prepolymer solution that meets the requirements can be obtained at room temperature by ultrasonic combined with mechanical stirring. The preparation method is more flexible and simple.

[0073] In some optional embodiments, the modifier includes styrene acrylic emulsion and dimethyl acrylamide, wherein the dimethyl acrylamide is used to adjust the rigidity of the styrene acrylic emulsion, and the mass percentage of the dimethyl acrylamide in the styrene acrylic emulsion is 1%-5%, preferably 2%-3%, which can improve the mechanical properties of the polymer current collector 10 and improve the adhesion of the organic substrate, thereby increasing the service life of the battery. The crosslinking agent includes: dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea; the adhesive accounts for 1%-5% of the mass percentage of the prepolymer solution, and the mixture of dihydroxymethylurea or dihydroxymethylurea and monohydroxymethylurea can adjust the crosslinking degree of the reaction system, thereby effectively improving the chemical bonding between the reactants and promoting the formation of a spatial network structure, thereby effectively improving the viscosity of the prepolymer solution, thereby adjusting the viscosity of the crosslinked film; the thickener includes carboxymethyl cellulose, and the carboxymethyl cellulose accounts for 0.5%-5% of the mass percentage of the prepolymer solution. The thickener is used to adjust the viscosity of the prepolymer solution.

[0074] It has been experimentally verified that the cross-linked film 12 can reduce the damage to the organic substrate 11 during the sputtering of the conductive layer 2 during the preparation of the composite current collector 10. Through the cross-linked film 12 as described above, when the composite current collector formed is a positive composite current collector, the first conductive layer is aluminum, the longitudinal tensile strength MD of the positive composite current collector is ≥240MPa, and the transverse tensile strength TD is ≥200MPa; or, when the composite current collector formed is a negative composite current collector, the first conductive layer is copper, and the longitudinal tensile strength MD of the negative composite current collector is ≥220MPa, and the transverse tensile strength TD is ≥180MPa. Compared with the composite current collector without a cross-linked film, the mechanical tensile performance is greatly improved.

[0075] In addition, the cross-linked polymer of the cross-linked film 12 has good thermal stability, which can increase the glass transition temperature of the organic substrate 11, thereby improving the thermal stability of the organic substrate; and the cross-linked polymer of the cross-linked film 12 has good adhesion relative to the organic substrate, which can increase the bonding force between the organic substrate 11 and the conductive layer 2, thereby preventing the conductive layer 2 from falling off the organic substrate 11 during use, thereby improving the conductivity and safety of the battery.

[0076] In some preferred embodiments, the thickness of the polymer composite layer 1 is 4.3-10.8 μm, wherein the thickness of the organic substrate is 4-10 μm, and the thickness of the cross-linked film is 0.3-0.8 μm. The thickness of the cross-linked film 12 is relatively small, and the thickness of the cross-linked film 12 is negligible relative to the thickness of the organic substrate 11 in increasing the overall thickness of the composite current collector. While increasing the bonding force between the organic substrate 11 and the conductive layer 2, the thermal stability of the organic substrate 11, and the mechanical properties of the composite current collector, the increase in the thickness and weight of the composite current collector 10 is basically negligible. The thickness of the polymer composite layer 1 is micrometer-level, thereby reducing the thickness and weight of the composite current collector 10.

[0077] In some embodiments, the conductive layer may be a single conductive layer 2, such as Figure 1 and Figure 2As described in the embodiment shown, at this time, the material of the conductive layer 2 can be a metal or an alloy, preferably a metal. Metals include but are not limited to aluminum, copper, nickel, titanium, silver, etc., preferably aluminum and copper. Aluminum is cheap and has good conductivity, copper has good conductivity and corrosion resistance, and alloys include nickel-copper alloys, aluminum-zirconium alloys, etc. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, and the positive electrode current collector substrate selects PET or BOPET, which is low in price and has good stability. The conductive layer 2 is metal aluminum, and the metal aluminum is combined with PET or BOPET in the positive electrode for stable performance. The composite current collector 10 is used as a negative electrode current collector, and the negative electrode current collector substrate selects PP or BOPP, and the conductive layer 2 is metal copper, and the combination of copper and PP or BOPP has relatively stable performance. The conductive layer 2 is formed by directly depositing a metal layer on a polymer film by physical vapor deposition, and the film layer is relatively thin, for example, the thickness of the conductive layer 2 is 0.12 to 3 μm, and the optional thickness is 0.12 to 1 μm. The thinner metal conductive layer reduces the thickness and weight of the composite current collector as a whole.

[0078] In some embodiments, the conductive layer may be a composite conductive layer 2. The selection of the positive or negative current collector material as described above will result in a weak bonding force between the substrate and the metal layer, generally 0.2N / 15mm. In order to enhance the bonding force between the substrate and the metal layer, a composite conductive layer 2 may be used. Figure 3 and Figure 4 As shown, the conductive layer 2 includes a second conductive layer 21 and a first conductive layer 22, wherein the first conductive layer 22 is substantially equivalent to the single conductive layer described in the above embodiment, and the material of the first conductive layer 22 may be a metal or an alloy. The metal includes, but is not limited to, aluminum, copper, nickel, titanium, silver, etc., and the alloy includes a nickel-copper alloy, an aluminum-zirconium alloy, etc. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, and the first conductive layer 22 is metal aluminum; the composite current collector 10 is used as a negative electrode current collector, and the first conductive layer 22 is metal copper.

[0079] like Figure 3 or Figure 4 As shown, the second conductive layer 21 is disposed between the first conductive layer 22 and the cross-linked film 12. Since the metal conductive layer is directly deposited or sputtered on the cross-linked film 12, it may still not have sufficient viscosity. In order to further enhance the bonding force between the metal conductive layer and the cross-linked film 12, the second conductive layer 21 can be disposed. The material of the second conductive layer 21 includes but is not limited to metal oxides. The metal oxide is preferably but not limited to AlO xThe transition of the metal oxide can effectively improve the bonding force between the metal conductive layer and the organic substrate 11. In some embodiments, the second conductive layer 21 includes a metal oxide layer, and the metal oxide layer is formed on at least one surface of the cross-linked film 12 by an in-situ reaction. The metal oxide layer serves as the metal conductive material 22 and the second conductive layer of the cross-linked film 12, which enhances the bonding force between the first conductive layer 22 and the cross-linked film 12.

[0080] It can be understood that the second conductive layer 21 is an optional layer structure, see Figure 5 In some embodiments, the conductive layer 2 does not include the second conductive layer 21 , and the first conductive layer 22 is directly disposed on the surface of the cross-linked film 12 away from the organic substrate 11 .

[0081] See also Figure 6 In some optional embodiments, the first conductive layer 22 further includes a protective film 23 on the side away from the cross-linked film 12. The protective film 23 can prevent the first conductive layer 22 from being oxidized, corroded or damaged. The protective film 23 can be set on the outermost layer of the conductive layer 2. When the composite current collector is a positive composite current collector, when aluminum is selected as the first conductive layer, since aluminum itself will form an aluminum oxide protective layer, there is no need to set an additional protective film. However, when the composite current collector is a negative composite current collector, when copper is selected as the first conductive layer, since copper is easily corroded, a protective film needs to be set on the outside of copper.

[0082] Optionally, the thickness of the second conductive layer 21 is 0.01-0.1 μm, the thickness of the first conductive layer 22 is 0.1-1.5 μm, and the thickness of the protective film 23 is 0.01-1.4 μm. The thickness of the conductive layer 2 disclosed in the present invention is much smaller than the thickness of the traditional copper foil or aluminum foil current collector, thereby reducing the weight of the current collector and the battery, reducing the cost, and increasing the energy density of the battery.

[0083] After experimental verification, the bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 can reach 8N / 15mm. In some embodiments, the bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 is greater than or equal to 5.0N / 15mm and less than or equal to 8N / 15mm, which is much greater than the bonding force between the organic substrate and the conductive layer in the existing composite current collector.

[0084] According to the specific implementation of the present disclosure, Figure 7 As shown, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, comprising the following steps:

[0085] Step S1, providing an organic substrate;

[0086] Step S2, disposing a cross-linking film on at least one side of the organic substrate, configured to enhance the cross-linking performance of the organic substrate, includes the following sub-steps, see Figure 8 As shown:

[0087] Step S21, adding an adhesive, a modifier and a thickener to a solvent, and obtaining a prepolymer solution by ultrasonic combined with mechanical stirring at room temperature, wherein the adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution;

[0088] In some embodiments, step S21 includes: adding an adhesive, a modifier and a thickener to a solvent, stirring under closed conditions to obtain a prepolymer solution. The solvent can be selected according to actual needs to ensure that the cross-linking polymerization reaction can proceed. Preferably, the solvent is at least one of water or ethanol. The stirring method can be selected according to actual conditions. For example: ultrasonic stirring, electric stirring, mechanical stirring, etc. Preferably, ultrasonic stirring combined with mechanical stirring is used under closed conditions to uniformly mix the adhesive, modifier and thickener in the solvent.

[0089] Step S22 , coating the prepolymer solution on at least one side of the organic substrate to form a cross-linked film; preferably, but not limited to, using a micro gravure coater to uniformly coat the cross-linked polymer on at least one surface of the organic substrate 11 .

[0090] Step S3, providing a conductive layer on at least one side of the cross-linked film away from the organic substrate.

[0091] In some embodiments, the step S1 includes: providing an organic substrate, and performing a corona treatment on the organic substrate at a power of 2500-3500W.

[0092] In some embodiments, the step S22 includes: coating the cross-linked polymer on at least one surface of the organic substrate, and reacting and curing at 50° C.-100° C. for 3-6 minutes to form the cross-linked film.

[0093] The reaction curing time can be adjusted according to the actual situation. In some optional embodiments, the thermal curing can be performed by segmented gradient thermal curing, for example, first curing at 50°C-70°C for 1-2 minutes, then curing at 70°C-90°C for 1-2 minutes, and finally curing at 90°C-100°C for 1-2 minutes. The segmented gradient thermal curing can enhance the mechanical strength of the cross-linked film.

[0094] In some embodiments, step S3 includes the following sub-steps: Fig. 9 As shown:

[0095] Step S31, forming a second conductive layer of aluminum oxide or copper oxide on at least one surface of the cross-linked film by an in-situ reaction;

[0096] Step S32, depositing aluminum or copper on the surface of the second conductive layer away from the cross-linked film by physical vapor deposition, thereby forming a first conductive layer on the surface of the second conductive layer.

[0097] In step S3, a physical vapor deposition method (PVD) is used to form a first conductive layer 22 on the surface of the cross-linked film 12 or the second conductive layer 21 away from the organic substrate 11. More preferably, the first conductive layer 22 is formed on the surface of the cross-linked film 12 or the second conductive layer 21 away from the organic substrate 11 by evaporating metal. The evaporation method is preferably, but not limited to, resist evaporation, electron gun evaporation, etc.

[0098] In some embodiments, after step S3, the method further includes: forming a protective film on a surface of the conductive layer away from the organic substrate. The material of the protective film 23 includes but is not limited to aluminum oxide.

[0099] According to some embodiments of the present disclosure, the present disclosure further provides a composite pole piece, comprising the composite current collector 10 provided by any of the above schemes or the composite current collector 10 obtained by the preparation method of the composite current collector provided by any of the schemes.

[0100] According to some embodiments of the present disclosure, the present disclosure further provides a lithium battery, comprising the composite pole piece provided by any of the above schemes.

[0101] According to some embodiments of the present disclosure, the present disclosure further provides a method for preparing a composite pole piece, including the method for preparing a composite current collector provided by any of the above schemes.

[0102] According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing a lithium battery, including a method for manufacturing a composite pole piece provided by any of the above schemes.

[0103] The composite current collector 10 and its preparation process and test data are introduced below through specific embodiments:

[0104] Embodiment 1:

[0105] In this embodiment, the organic substrate 11 is a 6 μm thick PET film, and the cross-linked film 12 is located on the upper and lower surfaces of the PET film. The cross-linked film 12 includes a prepolymer solution formed by the reaction of styrene-acrylic emulsion and dimethyl acrylamide, dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea, and carboxymethyl cellulose in water / anhydrous ethanol. The thickness of the cross-linked film 12 is 0.5 μm. The second conductive layer 21 is a metal oxide AlO xThe second conductive layer 21 is formed on the upper and lower surfaces of the cross-linked film 12 away from the PET film by in-situ reaction. The thickness of the second conductive layer 21 is 0.05 μm. The first conductive layer 22 is metal Al and has a thickness of 1.0 μm.

[0106] In this embodiment, the preparation method of the composite current collector specifically includes:

[0107] Step S1, corona treatment of the PET film at 3000W; adding 10g of styrene acrylic emulsion and 0.5g of dimethyl acrylamide, 10g of dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea, and 10g of carboxymethyl cellulose to water / anhydrous ethanol, performing ultrasonic and mechanical stirring under closed conditions, and stirring at 80°C for 0.5h to obtain a prepolymer solution; using a micro gravure coater to uniformly coat the prepolymer solution on the upper surface and lower surface of the PET film, and then reacting and curing at 80°C for 6min to form a cross-linked film on the upper surface and lower surface of the PET film; and

[0108] AlO was sputtered on the cross-linked films on both the upper and lower surfaces of the PET film. x , forming a second conductive layer; and evaporating Al on the second conductive layer to obtain a composite current collector.

[0109] Embodiment 2:

[0110] The present embodiment 2 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a PET film with a thickness of 4.5 μm, and the conductive material layer 22 is metallic copper.

[0111] Embodiment 3:

[0112] The present embodiment 3 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a 4.5 μm thick BOPP film, and the conductive material layer 22 is metallic copper.

[0113] Comparative Example 1:

[0114] This comparative example is basically the same as Example 1, and the only difference is that the conductive layer of this comparative example is directly evaporated on the surface of the organic substrate, and there is no cross-linking film between the organic substrate and the conductive layer.

[0115] Comparative Example 2:

[0116] Comparative Example 2 is substantially the same as Example 2, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0117] Comparative Example 3:

[0118] Comparative Example 3 is substantially the same as Example 3, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0119] Table 1 Comparison of composite current collector performance

[0120]

[0121]

[0122] It can be seen from the performance comparison results of the composite current collector in Table 1 that the tensile strength of the composite current collector in Example 1 is 240MPa in the longitudinal direction, reaching 250MPa, and 200MPa in the transverse direction, reaching 230MPa, and has strong tensile properties. The tensile strength of the composite current collector of Comparative Example 1 is 240≥MD≥200, which is 200Mpa; 200≥TD≥180, which is 180Mpa. It shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector. The strength of the modified substrate in Example 1 is also significantly greater than the strength of the substrate in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector substrate. The bonding force between the modified conductive layer and the substrate in Example 1 is also significantly greater than the bonding force in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the bonding force between the conductive layer and the substrate. The thermal shrinkage rate of the modified substrate in Example 1 is also significantly smaller than that of the substrate in Comparative Example 1, indicating that the modified layer in the composite current collector disclosed in the present invention greatly improves the thermal shrinkage rate of the substrate.

[0123] Table 2 Comparison of composite current collector core performance

[0124]

[0125] It can be seen from the performance comparison results of the composite current collector battery cells in Table 2 that the initial discharge capacity of Examples 1-3 of the present application is greater than the initial discharge capacity of the corresponding Comparative Examples 1-3, indicating that the composite current collector battery cells formed in each embodiment of the present application have good discharge performance.

[0126] The initial charge and discharge efficiency of Examples 1-3 of the present application is greater than that of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0127] The number of cycles of the capacity retention rate of Examples 1-3 of the present application is greater than the number of cycles of the capacity retention rate of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0128] The energy density of Examples 1-3 of the present application is greater than the energy density of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good safety performance.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them; although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A composite current collector, characterized in that: include: An organic substrate and a cross-linked film disposed on at least one side of the organic substrate, wherein the cross-linked film is used to enhance the cross-linking performance of the organic substrate; A conductive layer, disposed on a side of the cross-linked film away from the organic substrate; The cross-linked film is formed by coating a prepolymer solution on at least one side of the organic substrate. The prepolymer solution is obtained by adding an adhesive, a modifier and a thickener to a solvent and stirring the prepolymer solution by ultrasound combined with mechanical stirring at room temperature. The adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution.

2. The composite current collector according to claim 1, characterized in that: The modifier comprises: styrene acrylic emulsion and dimethyl acrylamide, wherein the dimethyl acrylamide is used to adjust the rigidity of the styrene acrylic emulsion, and the mass percentage of the dimethyl acrylamide in the styrene acrylic emulsion is 2%-3%.

3. The composite current collector according to claim 2, characterized in that: The mass percentage of the styrene-acrylic emulsion to the prepolymer solution is 0.5%-10%.

4. The composite current collector according to claim 1, characterized in that: The adhesive comprises: dihydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea; the mass percentage of the adhesive in the prepolymer solution is 1%-5%.

5. The composite current collector according to claim 1, characterized in that: The thickener includes carboxymethyl cellulose, and the mass percentage of the carboxymethyl cellulose in the prepolymer solution is 0.5%-5%.

6. A composite pole piece, characterized in that: The composite pole piece comprises the composite current collector according to any one of claims 1 to 5.

7. A lithium battery, characterized in that: Including the composite pole piece as described in claim 6.

8. A method for preparing the composite current collector according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, providing an organic substrate; Step S2, disposing a cross-linking film on at least one side of the organic substrate, configured to enhance the cross-linking performance of the organic substrate, comprising: Step S21, adding an adhesive, a modifier and a thickener to a solvent, and obtaining a prepolymer solution by ultrasonic combined with mechanical stirring at room temperature, wherein the adhesive is used to enhance the viscosity of the prepolymer solution, the modifier is used to enhance the mechanical properties of the organic substrate, and the thickener is used to adjust the viscosity of the prepolymer solution; Step S22, coating the prepolymer solution on at least one side of the organic substrate to form a cross-linked film; Step S3, providing a conductive layer on at least one side of the cross-linked film away from the organic substrate.

9. A method for preparing a composite pole piece, characterized in that: A method for preparing the composite current collector according to claim 8.

10. A method for preparing a lithium battery, characterized in that: Including the method for preparing the composite pole piece as claimed in claim 9.